Use of materials of operational-search activities in the administrative process - Kharevich, Dmitry L. (Journal of the Belarusian State University. Law, 2024)
The problem of using materials of operational-search activity in the administrative process in accordance with the legislation of the Republic of Belarus is considered. In the absence of a direct ban on the use of materials of operational-search activities in the administrative process, the Law of the Republic of Belarus of 15 July 2015 No. 307-З «On operational-search activities», the Procedural and Executive Code of the Republic of Belarus on Administrative Offenses and the Criminal Procedure Code of the Republic of Belarus do not have norms allowing such use and regulating the relevant procedure. Recognising the inadmissibility of the purposeful implementation of operational-search activities to expose a person for committing an administrative offense (in the absence of signs of a crime), the author concludes that it is possible to use the materials of operational-search activities in the administrative process in cases where after the completion of the lawfully carried out operational-search activity, qualification of the act was changed from a crime to an administrative offense or signs of an administrative offense were found along the way when documenting the crime. Based on the analysis of the legal principles of observance of the rights, freedoms and legitimate interests of citizens, the rights and legitimate interests of organisations, proportionality (proportionality) and secrecy, proposals are formulated for legislative acts that establish the procedure for using materials of operational-search activities in the administrative process, which will increase the effectiveness of the fight against administrative offenses, to strengthen law and order.